Physicochemical characteristics of modified tapioca using microwave heating - Sangadji, Rosmiati; Polnaya, Febby J.; Tetelepta, Gilian (AGROMIX, 2024)
Introduction: This study aimed to assess the physicochemical characteristics of tapioca modified by microwave heat treatment. Methods: The assessment was carried out using a one-factor Completely Randomized Design, namely microwave heat treatment with four levels of commercial tapioca. These included microwave tapioca (TMW), microwave washing tapioca (TPMW), and microwave soaking tapioca (TPRMW) with three replications. The variables observed were chemical tests including moisture and ash content, with physical characteristics such as solubility, swelling power, water, and oil holding capacity (OHC). The data obtained were assessed using MINITAB 21 analysis of variance, followed by Tukey’s test when there was a significant difference. Results: The best treatment was found to be a modification of starch using microwave heat in TPRMW, producing 8.01% moisture content, 0.13% ash content, 32.80% swelling power, 24.76% solubility, 218.50% water holding capacity (WHC), and 176.93% OHC. Conclusion: Modification treatment using microwave heat caused chemical and physical changes in tapioca to experience a decrease in moisture content, ash content, swelling power, solubility, and OHC compared to natural tapioca. However, this treatment increased WHC, which was specifically observed for TPRMW.